Metabolic Syndrome in the Productive Age Group: A Holistic Health Promotion–Based Approach for Prevention and Management - Yunus, Moch.; Andyastanti, Tisnalia Merdya; Fanani, Erianto (PT FORMOSA CENDEKIA GLOBAL, 2025)
Metabolic syndrome is an increasingly common cluster of cardiometabolic risks among the productive-age population. This Systematic Literature Review (PRISMA) identified holistic, health promotion–based strategies for its management. From 511 articles screened, 26 met the inclusion criteria. The findings show that combined interventions—physical activity, healthy diets, continuous education, behavioral modification, and supportive environments and policies—significantly improve metabolic syndrome indicators, including blood pressure, lipid profile, and insulin sensitivity. The review emphasizes integrating multiple components and leveraging technology to strengthen adherence. Overall, a holistic health promotion approach is effective for preventing and reducing metabolic syndrome in productive-age adults and provides valuable guidance for policymakers and public health practitioners.